Biodiversity, social adoptability, and preference toward managing medicinal plants in homegardens across elevations in the Menoreh Mountains, Kulonprogo District, Indonesia - BUDIADI BUDIADI; SITI NURUL ROFIQO IRWAN; LINA DWI LESTARI; MUHAMMAD IQBAL NUR MADJID; HADI SUSILO ARIFIN; NURHAYATI NURHAYATI; KASWANTO KASWANTO; BUDI FAISAL; MUHAMMAD ZAINI DAHLAN; SITI RAHAYU NADHIROH; TUTIK SRI WAHYUNI; MUHAMMAD SADDAM ALI (Society for Indonesian Biodiversity, 2025)
Abstract. Budiadi, Irwan SNR, Lestari LD, Madjid MIN, Arifin HS, Nurhayati, Kaswanto, Faisal B, Dahlan MZ, Nadhiroh SR, Wahyuni TS, Ali MS. 2025. Biodiversity, social adoptability, and preference toward managing medicinal plants in homegardens across elevations in the Menoreh Mountains, Kulonprogo District, Indonesia. Biodiversitas 26: 1316-1324. Pekarangan, or